STRATEGI PENGEMBANGAN PRODUK DI INDUSTRI MEDIA CETAK DI INDONESIA (Bertahan di tengan Persaingan Media Online - Sholahuddin, Sholahuddin (Benefit: Jurnal Manajemen dan Bisnis, 2013)
Understanding the printing press industry position in the product life cycle is veryÂ important. This is to determine the right strategy for the printing press in order to be exist andÂ profitable. When we see the condition of the printing press which is facing tough competition withinternet-based media beside the uncertain challenge ahead, the printing press industry is in thematurity phase. In this position is required precise product development strategy. The strategy canbe done by creating new products with expands in a press online and by improving the quality,either by changes in product design or improvement of product quality print journalism.